2021
DOI: 10.1186/s12960-021-00599-8
|View full text |Cite
|
Sign up to set email alerts
|

Professional integration of immigrant medical professionals through alternative career pathways: an Internet scan to synthesize the current landscape

Abstract: Background There is a growing recognition that underutilization and underemployment of skilled immigrants, especially internationally trained health professionals, creates a financial burden on individuals and economic losses for the host country. Albeit a missed opportunity for both the immigrants and the receiving country, no public policy and systemic measures are in place to address this issue. Nevertheless, certain individuals and organizations have made some isolated efforts, but no synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It has been reported that IMGs generally seldom considered seeking any career other than becoming a physician [ 7 ], and this usually leads to delay in seeking any other career [ 8 ]. This delay can deprive IMGs of time that may be required to prepare for any new career and obtain any required related work training or experience to allow for success in a decent alternative career [ 9 , 10 ]. Most studies on IMGs only focused on the areas of work [ 11 , 12 ] and experience of the licensed IMGs [ 13 ] and barriers and struggles [ 14 ] to licensing for the unlicensed IMGs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IMGs generally seldom considered seeking any career other than becoming a physician [ 7 ], and this usually leads to delay in seeking any other career [ 8 ]. This delay can deprive IMGs of time that may be required to prepare for any new career and obtain any required related work training or experience to allow for success in a decent alternative career [ 9 , 10 ]. Most studies on IMGs only focused on the areas of work [ 11 , 12 ] and experience of the licensed IMGs [ 13 ] and barriers and struggles [ 14 ] to licensing for the unlicensed IMGs.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a proper understanding about the job market and lack of a clear understanding of where they stand as job candidates also impacts IEPs’ preparation for any job application or interview [ 3 ]. Inadequately researching and exploring the specifics of an alternative job, failing to obtain the required training/volunteer experience for the job, applying for the job with an inappropriate resumé for the particular job, and being underprepared for interviews are all aspects of the job search process that have been observed to be negatively affecting the IEPs’ job search performance.…”
Section: Alternative Career Pathways In the Health And Wellness Sectormentioning
confidence: 99%
“…The immigrant population is often an excellent pool of human resources with diverse skills and expertise. Amongst these highly skilled immigrants are internationally educated physicians (IEP), international medical graduates, or foreign medical graduates “who gained their qualifications from a medical school in a country other than the one in which they seek to professionally integrate” [ 2 , 3 ]. In 2017/18, more than one in six doctors working in an Organisation for Economic Co-operation and Development (OECD) country, which includes Canada, the USA, the UK, Australia, New Zealand, and more, had obtained their medical degree in another country, up from one in seven a decade earlier [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our community-engaged research programme on immigrant/ethnic-minority community issues, we conducted a range of studies on health and wellness issues as well as integration and resettlement, including studies on equitable access to health care9–12 and labour market integration for internationally trained health professionals 13 14. We conducted studies where we explored the challenges and unmet needs faced by Bangladeshi-Canadians when accessing healthcare 9 10.…”
Section: Introductionmentioning
confidence: 99%